Effects of fortified milk on morbidity in young children in north India: community based, randomised, double masked placebo controlled trial. Issue 7585 (28th November 2006) - Sazawal, Sunil; Dhingra, Usha; Dhingra, Pratibha; Hiremath, Girish; Kumar, Jitendra; Sarkar, Archana; Menon, Venugopal P; Black, Robert E
Abstract : Objective To evaluate the efficacy of milk fortified with specific multiple micronutrients on morbidity in children compared with the same milk without fortification. Design Community based, double masked, individually randomised trial. Setting Peri-urban settlement in north India. Participants Children (n=633) aged 1-3 randomly allocated to receive fortified milk (n=316) or control milk (n=317). Intervention One year of fortified milk providing additional 7.8 mg zinc, 9.6 mg iron, 4.2 µg selenium, 0.27 mg copper, 156 µg vitamin A, 40.2 mg vitamin C, 7.5 mg vitamin E per day (three feeds). Main outcome measures Days with severe illnesses, incidence and prevalence of diarrhoea, and acute lower respiratory illness. Results Study groups were comparable at baseline; compliance in the groups was similar. Mean number of episodes of diarrhoea per child was 4.46 (SD 3.8) in the intervention (fortified milk) group and 5.36 (SD 4.1) in the control group. Mean number of episodes of acute lower respiratory illness was 0.62 (SD 1.1) and 0.83 (SD 1.4), respectively. The fortified milk reduced the odds for days with severe illnesses by 15% (95% confidence interval 5% to 24%), the incidence of diarrhoea by 18% (7% to 27%), and the incidence of acute lower respiratory illness by 26% (3% to 43%). Consistently greater beneficial effects were observed in children aged ≤24 months than in older children. Conclusion Milk is well accepted as a means of delivery of micronutrients. Consumption of milk fortified with specific micronutrients can significantly reduce the burden of common morbidities among preschool children, especially in the first two years of life. Trial registration NCT00255385 .